GIRL TALK: ENGLISH IN MODERN MEANS OF COMMUNICATION - Palibrk Ивана; Tošić Тиана (Наслеђе, 2012)
The paper takes into account recent sociolinguistic gender studies as well as the widespread usage of English language in the speech of younger Serbian population in regard to the language of social networks and text messages. We emphasize the discourse of young females aged between 15 and 25 – its tendency towards the nonstandard forms, yet preserving solidarity and the role of English in those. The aim is to present the distinguishing features of female discourse, primarily on lexical level, for the purpose of which quantitative analysis is going to be used. We expect to determine the extent and the structure of the “borrowed” linguistic inventory and clarify the cause of such a selection.